Nurses’ Compliance with Principles of Documentation: A Descriptive, Short Observational Study from Oman - AL Nasri, Amira; AL Araimi, Alya; AL Kitani, Tahani; AL Wahaibi, Abayada; AL Zarai, Nassra; AL Senaidi, Raya; AL Bahlooli, Muna; AL Hakmani, Salma; AL Balushi, Ahmed; AL Humaidi, Azmi (British Journal of Healthcare and Medical Research, 2026)
Background: Nursing documentation is a critical component of patient care, communication, and legal accountability. Inadequate documentation compromises patient safety and quality of care. Objective: To assess nurses’ compliance with principles of nursing documentation. To correlate the demographic characteristics with the quality of nursing documentation. Methods: A descriptive, quantitative observational study was conducted using patient records documented by nurses over a defined period in multicenter at primary health care institution, South Sharqyiah. Documentation was assessed using a structured audit checklist based on established documentation principles. Descriptive and inferential statistics were used for analysis. Results: A total of 273 nurses were observed for their documentation post care delivery for a defined period. Overall compliance with documentation principles was moderate (71.3%). The study findings indicated varying levels of compliance with documentation principles. High compliance was observed in general structure and quality of documentation such as’’ Document is entered by staff who delivered the care’’ (mean=1.99, SD=0.12); Document is stated in specific, concise, accurate manner (mean=1.96, SD=0.20), while The lowest scores in the entire audit were found in documenting pain assessment (mean=1.26). Low scores in nursing documentation were also found in nursing process, psychological support, procedural notes contain details of intervention (mean=1.38) for each one. Providing health education, and communication with clients/ family were also got low scores (1.39, 1.46) respectively. In regards to documentation of vital signs, the highest scores of documentation was blood pressure (1.81), whereas the lowest was documenting respiratory rate (1.53) and documenting consciousness level of the patient (1.01) . The quantitative data also illustrates that only 98 (36%) of nurses had in service training related to nursing documentation. Significant associations were found between quality of documentation and demographic characteristics include nationality, education, institution category (p < 0.05). Conclusion: Nurses’ compliance with documentation principles was suboptimal in several areas. This study found a critical gap in nursing documentation related to documenting psychological care, health education and nurse/patient communication, which recommend to re-assess the current policies and protocols and modify them accordingly. Strengthening training, supervision, and standardized documentation tools are also recommended to improve documentation quality and patient safety.